The Medieval Kingdom of Sicily Image Database. (3rd April 2019) - Bruzelius, Caroline; Vitolo, Paola
Abstract : The Medieval Kingdom of Sicily Image Database documents historic buildings, monuments, and their decoration in South Italy, a geographic area ravaged by war, earthquakes, volcanic eruptions, as well as the depredations of modern restoration and rampant urban growth. Our website and app are intended to help scholars, travelers, and local populations understand the appearance of historic monuments prior to modern change: their position in the landscape, their rich furnishings (tombs, altars, pulpits, painted ceilings, mosaics, altarpieces), and their role as statements of dynastic authority.